2021
DOI: 10.1021/acs.iecr.1c01317
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid Models Based on Machine Learning and an Increasing Degree of Process Knowledge: Application to Capture Chromatographic Step

Abstract: In process engineering, two paradigms of modeling approaches exist: the mechanistic and the data-driven approaches with the former being completely based on knowledge while the latter completely based on data. In our previous work, we highlighted the advantages of using hybrid models that explores the synergy between mechanistic and data-driven models. Here we introduce the concept of developing a series of hybrid models constituted by a progressively increasing extent of process knowledge. Thus, aligning the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 39 publications
0
37
0
Order By: Relevance
“…The more knowledge about a certain process is available, the fewer experiments have to be performed when hybrid modeling approaches are chosen to develop a well-performing model ( Yang et al, 2015 ; Bayer et al, 2020c ; Smiatek et al, 2020 ). Recently, the incorporation of mechanistic understanding at different levels in different hybrid modeling approaches was evaluated for chromatography ( Narayanan et al, 2021a ). Moreover, Krippl et al (2020) could demonstrate that by using hybrid modeling, different tangential flow filtration operational modes can be described from the same training data set.…”
Section: Introductionmentioning
confidence: 99%
“…The more knowledge about a certain process is available, the fewer experiments have to be performed when hybrid modeling approaches are chosen to develop a well-performing model ( Yang et al, 2015 ; Bayer et al, 2020c ; Smiatek et al, 2020 ). Recently, the incorporation of mechanistic understanding at different levels in different hybrid modeling approaches was evaluated for chromatography ( Narayanan et al, 2021a ). Moreover, Krippl et al (2020) could demonstrate that by using hybrid modeling, different tangential flow filtration operational modes can be described from the same training data set.…”
Section: Introductionmentioning
confidence: 99%
“…As next steps, further robustness can be added into the surrogate model by incorporating physically relevant constraints (e.g., physiological osmolality) and information gained by experience (Figure E). Such approaches are gaining popularity in bioprocessing under the so-called “hybrid modeling” framework, which combines knowledge-based and data-driven models. Extending this concept to formulation optimization will be a very interesting direction of future works.…”
Section: Discussionmentioning
confidence: 99%
“…[7,8] The increasing computing power has allowed researchers to revisit hybrid modelling with a different perspective. For instance, Narayanan et al [9,10] were able to use a hybrid strategy within a system of partial differential equations (PDE) to describe the single-component adsorption in a fixed bed unit. The hybrid strategy provided notable results in modelling the system.…”
Section: Introductionmentioning
confidence: 99%
“…In this work, we extended the MTI-hybrid strategy to a multicomponent scenario. Furthermore, Narayanan et al [9,10] pointed out that the MTI-hybrid required a pre-identified adsorption model to be used as an initial guess for the hybrid model training.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation